Multinational enterprises and new trade theory: Evidence for the convergence hypothesis - Salvador Barrios Cobos; Holger Görg; Eric Strobl (Centre for Economic Policy Research (CEPR), 2001)
According to the `convergence hypothesis', multinational companies will tend to displace national firms and trade as total market size increases and as countries converge in relative size, factor endowments, and production costs. Using a recent model developed by Markusen and Venables (1998) as a theoretical framework, we explicitly develop and address the properties of empirical measures to proxy displacement of national by multinational firms between two countries. These empirical measures are then used to test the convergence hypothesis for a panel of data of country pairs over the years 1985–96. Our results provide some empirical support for the convergence hypothesis.
Keywords: F21; F23; 330; Multinationales Unternehmen; Neue Außenhandelstheorie; Theorie